Benzimidazole resistance-associated mutations improve the in silico dimerization of hookworm tubulin: An additional resistance mechanism - Jan Clyden B. Tenorio; Muhammad Fikri Heikal; Alok Kafle; Prasert Saichua; Sutas Suttiprapa (Veterinary World)
Background and Aim: Mutations in the β-tubulin genes of helminths confer benzimidazole (BZ) resistance by reducing the drug’s binding efficiency to the expressed protein. However, the effects of these resistance-associated mutations on tubulin dimer formation in soil-transmitted helminths remain unknown. Therefore, this study aimed to investigate the impact of these mutations on the in silico dimerization of hookworm α- and β-tubulins using open-source bioinformatics tools.